A false image of health: how fake news and pseudo-facts spread in the health and beauty industry. Issue 2 (8th August 2019) - de Regt, Anouk; Montecchi, Matteo; Lord Ferguson, Sarah
Abstract : Purpose: Diffusion of fake news and pseudo-facts is becoming increasingly fast-paced and widespread, making it more difficult for the general public to separate reliable information from misleading content. The purpose of this article is to provide a more advanced understanding of the underlying processes that contribute to the spread of health- and beauty-related rumors and of the mechanisms that can mitigate the risks associated with the diffusion of fake news. Design/methodology/approach: By adopting denialism as a conceptual lens, this article introduces a framework that aims to explain the mechanisms through which fake news and pseudo-facts propagate within the health and beauty industry. Three exemplary case studies situated within the context of the health and beauty industry reveal the persuasiveness of these principles and shed light on the diffusion of false and misleading information. Findings: The following seven denialistic marketing tactics that contribute to diffusion of fake news can be identified: (1) promoting a socially accepted image; (2) associating brands with a healthy lifestyle; (3) use of experts; (4) working with celebrity influencers; (5) selectively using and omitting facts; (6) sponsoring research and pseudo-science; and (7)exploiting regulatory loopholes. Through a better understanding of how fake news spreads, brand managers can simultaneously improve the optics that surround their firms, promote sales organically and reinforce consumers' trust toward the brand. Originality/value: Within the wider context of the health and beauty industry, this article sets to explore the mechanisms through which fake news and pseudo-facts propagate and influence brands and consumers. The article offers several contributions not only to the emergent literature on fake news but also to the wider marketing and consumer behavior literature.